(3CSeGA Gddg GdMSfis
(3ChdgG (B:s
(3hddg GdCSeGA GdoMSfi aGOYhg HgG Gddge EfG fSCdc jGGddg jGQMef jGQMje jGedc jGbOhS s
(3BNQgG (B:s
(3hdGMhd hdGbhI EdG HGddg GdYdj GdYXje SHMGfc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJUha hGdBOGH GdTQYjIs